(untitled) (Resunga Journal रेसुङ्गा जर्नल, 2024)
This article aims to determine the major mental health problems and their impact on human health and socio- economic condition of residents in Gulmi District. It explores individual’s thoughts, feelings, and experiences to gain insights into specific psychological phenomena. It also informs about the preventive measures to determine factors associated with it and improve health and quality of life for people affected by these conditions. This proposed research study consists of a description and an in-depth analysis of the ethics of the study.